Peran BPD Dalam Pengawasan Bantuan Nelayan Desa Bumbulan Kecamatan Paguat Kabupaten Pohuwato - Muhamad Afik Naha; Syarwani Canon; Irwan Yantu (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2020)
The purpose of this qualitative descriptive study was to determine the role and supervision of the Village’s consultative Agency of fisherman assistance. Data collection techniques used were observation, interviews, and documentation. The result showed: 1. The role of Village’s Consultative, 2. The inhibiting factors for the BPD in the village government program regarding fisherman assistance.